HUBUNGAN PENGETAHUAN, PEKERJAAN IBU, DAN STATUS EKONOMI DENGAN PEMBERIAN ASI EKSKLUSIF - Jannah, Miftahul (JURNAL KESEHATAN TERAPAN, 2021)
Background: The Program for Increasing the Use of Mother's Milk (PP – ASI), especially Exclusive Breastfeeding is a priority program, because it has a broad impact on the nutritional status and health of children under five. This priority program is also related to global agreements, including the 1990 Innocentipula Declaration (Italy) on the protection, promotion and support of breastfeeding, which also agreed to achieve 80% exclusive breastfeeding. (Roesli, 2007). Objective: To determine the relationship between knowledge, mother's occupation, and economic status with exclusive breastfeeding. Methods: Analytical survey with a cross sectional approach with a population of 50 respondents, the number of samples taken from the accidental sampling technique. The results of univariate, bivariate and chi-square statistical tests showed that there was a significant relationship between knowledge and p value 0.014 < 0.05, and there was no significant relationship between occupation, p value 0.000 < 0.05, there was a relationship between economic status and p-value 0.045 <0.05 with Exclusive Breastfeeding. Suggestion: It is expected for health workers to further improve the quality of health services by promoting health to mothers by maintaining especially the importance of routinely giving exclusive breastfeeding to infants so that it is expected to reduce the rate of disability in infants. Keywords: Exclusive Breastfeeding